ABOUT MACROECONOMIC PURPOSE OF THE STRATEGIC DEVELOPMENT OF EFFECTIVE BALANCED MACROECONOMIC SYSTEMS - Sergey A. Vladimirov (Статистика и экономика)
The purpose of this article is a theoretical substantiation of the possibility of DOS reaches the maximum possible public efficiencies of government spending, investments and taxes in perfect condition coordination bath open economic system. The proposed model can always bring in the ideal case («zero-loss" public effectively scope of public expenditure and investment) to the maximum possible rate of economic growth, that allows you to substantiate the main directions of the relevant macroeconomic (fiscal, tax and budget) policy.